Exploring Teachers' Perceptions of the Relevance of African Languages in the Digital Space - Calsile Khumalo; Maglin Moodley (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Digital learning is the future of education within the African context, and thus it is important to provide equitable access to educational content for all African language speaking students. By so doing, the quality of education and the relevance of African languages will be enhanced. This study aimed to explore the perceptions of teachers towards the relevance of African languages in the digital space.Â The study adopted a mixed methods technique and chose a sample of 10 language teachers from four high schools for the online survey and semi-structured interviews. The online survey data was analysed using descriptive statistics, whilst the interview data was analysed using thematic analysis. The studyâ€™s key findings showed that while the teachers were happy to see African languages being used on a digital platform, they advocated further for the empowering of African languages. However, there was a sentiment amongst majority of participating teachers that while African languages are important, they are however not relevant in the 21st century and that their integration onto digital platforms might be nice-to-have, but in the larger scope of things they will not prepare students for the 21st century. The findings were explained against the theory of Colonial Mentality.Â